2020
DOI: 10.1016/j.kint.2020.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose L-NAME induces salt sensitivity associated with sustained increased blood volume and sodium-chloride cotransporter activity in rodents

Abstract: To investigate the cause of salt sensitivity in a normotensive animal model, we treated rats with a low-dose of the nitric oxide synthase inhibitor, L-NAME, that does not elevate blood pressure per se or induce kidney fibrosis. A high salt diet increased the circulating blood volume both in L-NAMEtreated and nontreated animals for the first 24 hours. Thereafter, the blood volume increase persisted only in the L-NAME-treated rats. Blood pressure was higher in the L-NAMEtreated group from the start of high salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Nitric Oxide (NO) is a potent vasodilator proposed to be a key regulator of vascular tone in salt sensitivity (Bech et al, 1998). In this regard, an important model of salt sensitivity that has been widely used includes a low dose of the nitric oxide synthase inhibitor, L-NAME, that does not elevate blood pressure per se, followed by a high salt diet (Itani et al, 2016;Van Beusecum et al, 2019;Wang et al, 2020). This model demonstrated increased blood pressure in response to salt intake due to subnormal vasodilatory responses combined with a normal saltand salt-induced hypervolemia.…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric Oxide (NO) is a potent vasodilator proposed to be a key regulator of vascular tone in salt sensitivity (Bech et al, 1998). In this regard, an important model of salt sensitivity that has been widely used includes a low dose of the nitric oxide synthase inhibitor, L-NAME, that does not elevate blood pressure per se, followed by a high salt diet (Itani et al, 2016;Van Beusecum et al, 2019;Wang et al, 2020). This model demonstrated increased blood pressure in response to salt intake due to subnormal vasodilatory responses combined with a normal saltand salt-induced hypervolemia.…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…This model demonstrated increased blood pressure in response to salt intake due to subnormal vasodilatory responses combined with a normal saltand salt-induced hypervolemia. Interestingly, controls' blood volume reductions were associated with elevated urinary sodium excretion, indicating that high blood pressure, sodium retention, and hypervolemia are necessary (Wang et al, 2020).…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…Moreover, NO prevents lipid peroxidation and inhibits the formation of lipid peroxidation products like isoprostanes and isoketals, which are immunogenic in DCs. Another important pathogenic event resulting from low-dose L-NAME is vascular dysfunction ( Wang et al, 2020 ). In that regard, rats treated with a low dose of L-NAME demonstrated Subnormal vasodilation and elevated BP in response to a salt load ( Wang et al, 2020 ).…”
Section: Animal Models Of Salt-sensitive Hypertensionmentioning
confidence: 99%
“…Another important pathogenic event resulting from low-dose L-NAME is vascular dysfunction ( Wang et al, 2020 ). In that regard, rats treated with a low dose of L-NAME demonstrated Subnormal vasodilation and elevated BP in response to a salt load ( Wang et al, 2020 ). Interestingly, in that study, volume expansion was comparable between the two groups on day 1, suggesting that vascular dysfunction was responsible for the initiation of salt-sensitive HTN.…”
Section: Animal Models Of Salt-sensitive Hypertensionmentioning
confidence: 99%
“…7 Long non-coding RNAs (lncRNAs) are a subset of non-coding RNA molecules of about 200 nt, and studies have shown that lncRNAs play important roles in many life processes such as epigenetic regulation, cell cycle regulation, and cell differentiation regulation. [8][9][10] LncRNAs are involved in tumorigenesis, development, and metastasis processes. 11,12 Currently, studies on iron death-related lncRNAs are limited.…”
Section: Introductionmentioning
confidence: 99%